KAJIAN SIFAT FISIKA TANAH PADA AREAL TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) YANG SUDAH TIDAK PRODUKTIF DI KEBUN PTP. NUSANTARA II TANJUNG GARBUS The Study of Soil Physical properties in undproductive oil palm plantations (Elaeis guin - Abd Musowwir; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2018)
ABSTRACT Soil physical properties is an important factor for plant growth. The research was aimed to examine the soil physical properties in undproductive oil palm plantation (Elaeis guineensis Jacq.) at PTP. Nusantara II Tanjung Garbus. The research used survey and soil analysis methods and conducted at the Research and Technology Laboratory of the Faculty of Agriculture, University of Sumatera Utara and Research Center Laboratory of palm oil research centre in Medan. The parameters observed were soil texture, organic matter, porosity, depth of soil effectiveness, soil permeability and water availabilety. The results showed that the type of the soil on Afd. 3 PTP. Nusantara II Tanjung Garbus was Entisol, with sand clay at a depth of 5 cm and clay sandy at a depth of 25 cm, the content of organic materials at a depth of 5 cm was ranged from 1.41 % – 2.36 % and at a depth of 25 cm was ranged from 0.07 % - 1.14 %, porosity of soil at a depth of 5 cm was ranged from 46.60 % – 52.88 % and at a depth of 25 cm was ranged from 44.78% – 47.62 % with effective depth of soil in ferns, grass and reeds were 62 cm, 68 cm and 64 cm, soil permeability at a depth of 5 cm was ranged from 5.67 cm/hr – 19.76 cm/hr and at a depth 25 cm was range from 0.33 cm/hr – 0.86 cm/hr, the amount of water available for vegetated fields of grasses, grasses and reeds were 11.58%, 5.19% and 7.3%. Keywords : entisol, oil palm,physical properties of soil, PTP. Nusantara II Tanjung Garbus Estate, unproductive ABSTRAK Sifat fisika tanah merupakan faktor penting bagi pertumbuhan tanaman. Penelitian ini bertujuan untuk mengkaji sifat fisika tanah pada areal tanaman kelapa sawit (Elaeis guineensis Jacq.) yang sudah tidak produktif di kebun PTP. Nusantara II Tanjung Garbus. Penelitian menggunakan metode survei dan analisa tanah dilakukan di Laboratorium Riset dan Teknologi Fakultas Pertanian Universitas Sumatera Utara dan Laboratorium Pusat Penelitian Kelapa Sawit Medan. Parameter yang diamati meliputi tekstur tanah, bahan organik, porositas, kedalaman efektif tanah, permeabilitas tanah dan air tersedia. Hasil penelitian menunjukkan jenis tanah pada lahan Afd. 3 PTP. Nusantara II Tanjung Garbus adalah Entisol, bertekstur pasir berlempung pada kedalaman 5 cm dan lempung berpasir pada kedalaman 25 cm, kandungan bahan organik pada kedalaman 5 cm berkisar antara 1,41 % - 2,36 % dan pada kedalaman 25 cm berkisar antara 0,07 % - 1,14 %. Porositas tanah pada kedalaman 5 cm berkisar antara 46,60 % - 52,88 % dan pada kedalaman 25 cm berkisar antara 44,78 % - 47,62 %, kedalaman efektif tanah pada pakis, rumput dan ilalang yaitu 62 cm, 68 cm dan 64 cm, permeabilitas tanah pada kedalaman 5 cm berkisar antara 5,67 cm/jam - 19,76 cm/jam dan pada kedalaman 25 berkisar antara 0,33 cm/jam – 0,86 cm/jam, Jumlah air tersedia untuk lahan bervegetasi pakis, rumput dan ilalang yaitu 11,58 %; 5,19 % dan 7,3 %. Kata Kunci: entisol, kebun PTP. Nusantara II Tanjung Garbus, kelapa sawit, sifat fisika tanah, tidak produktif..